Association of Circulating Omentin-1 with Osteoporosis in a Chinese Type 2 Diabetic Population - Pijun Yan; Yong Xu; Zhihong Zhang; Jianhua Zhu; Ying Miao; Chenlin Gao; Qin Wan (Hindawi Limited, 2020)
Aims. Omentin-1, a newly identified adipokine, has been demonstrated to be associated with bone metabolism, but the results have been inconsistent. Moreover, the potential relationship of circulating omentin-1 with diabetic osteoporosis has never been reported. This study is intended for studying the association between circulating omentin-1, bone mineral density (BMD), prior fragility fractures, and other bone metabolic-related parameters. Methods. Circulating omentin-1 levels were measured in 172 patients with type 2 diabetes mellitus (T2DM), and participants were divided into the normal BMD group (n=52), the osteopenia group (n=66), and the osteoporosis group (n=54). The relationship between circulating omentin-1 and diabetic osteoporosis and other parameters was analyzed. Results. Circulating omentin-1 was significantly higher in the osteoporosis group than in the normal group and in the osteopenia group (both P<0.05). Circulating omentin-1 levels were correlated significantly and positively with sex; high-density lipoprotein cholesterol; apolipoprotein A; and prevalence of prior fragility fractures, diabetic nephropathy, and retinopathy; they were correlated negatively with diastolic blood pressure, triglyceride, hemoglobin, atherogenic index of plasma, osteoporosis self-assessment tool for Asians, BMD at different skeletal sites, and corresponding T scores, irrespective of age, sex, and body mass index (P<0.01 or P<0.05). Moreover, circulating omentin-1 was an independent decisive factor for the presence of osteoporosis only in women after multivariate adjustment (odds ratio: 1.069; 95% confidence interval: 1.003-1.139; P<0.05). Lastly, the analysis of receiver operating characteristic curves revealed that the best cutoff value for circulating omentin-1 to predict diabetic osteoporosis was 15.37 ng/mL (sensitivity: 71.7%; specificity: 58.5%) in female subjects. Conclusions. High levels of circulating omentin-1 may be associated with the development of osteoporosis in female diabetic subjects and may be a potential biomarker for diabetic osteoporosis in women.